Revealing methyl-esterification patterns of pectins by enzymatic fingerprinting: Beyond the degree of blockiness. (1st February 2022) - Jermendi, Éva; Beukema, Martin; van den Berg, Marco A.; de Vos, Paul; Schols, Henk A.
Abstract: Citrus pectins were studied by enzymatic fingerprinting using a simultaneous enzyme treatment with endo -polygalacturonase (endo-PG) from Kluyveromyces fragilis and pectin lyase (PL) from Aspergillus niger to reveal the methyl-ester distribution patterns over the pectin backbone. Using HILIC-MS combined with HPAEC enabled the separation and identification of the diagnostic oligomers released. Structural information on the pectins was provided by using novel descriptive parameters such as degree of blockiness of methyl-esterified oligomers by PG (DBPGme ) and degree of blockiness of methyl-esterified oligomers by PL (DBPLme ). This approach enabled us to clearly differentiate citrus pectins with various methyl-esterification patterns. The simultaneous use of PG and PL showed additional information, which is not revealed in digests using PG or PL alone. This approach can be valuable to differentiate pectins having the same DM and to get specific structural information on pectins and therefore to be able to better predict their physical and biochemical functionalities. Graphical abstract: Unlabelled Image